An amphiphilic ratiometric fluorescent probe with aggregation-induced emission feature for specific detection of hypochlorite in aqueous solution and living cells. (November 2022) - Fu, Juan; Hu, Xin; Liang, Ye; Guo, Teng; Deng, Fengjie; Zhu, Weifeng; Liu, Meiying; Wen, Yuanqing; Zhang, Xiaoyong; Wei, Yen
Abstract: Hypochlorite (ClO − ) as one of reactive oxygen species (ROS), that has been widely used in our daily life and played a crucial role in immune function systems of living organisms. However, due to the hydrophobic nature of most fluorescent probes, direct utilization of these probes for detection of ClO − in biological systems has demonstrated to be problem. In this work, hydrophilic amino-terminated polyethylene glycol (PEG-NH2 ) and the organic dye (named as TPAMA) with aggregation-induced emission (AIE) feature were conjugated together using hexachlorocyclotriphosphazene (HCCP) as linking agent. The resultant probe (named as TPAMA-HCCP-PEG) was examined as ratiometric fluorescent probe for detection of ClO − in pure aqueous solution by taking advantage of its amphiphilic property. After adding ClO −, the fluorescence of TPAMA was quickly quenched, therefore it can be used for sensing ClO − with high sensitivity and selectivity. The mechanism was attributed to the reaction of TPAMA with ClO −, resulting in a blue-shift in absorbance and fluorescence emission. The potential of TPAMA-HCCP-PEG for sensing ClO − in biological systems was also evaluated further. Results showed that TPAMA-HCCP-PEG could form highly dispersible nanoparticles in aqueous solution and displayed low cytotoxicity towards model cancer cell lines, making it promising for monitoring ClO − in living systems. We believe this work will provide a general tool for fabrication of fluorescent probes suitable for visual detection various molecules with important biological roles. Graphical abstract: Image 1 Highlights: The fluorescent probe with aggregation-induced emission was designed and synthesized. The fluorescent probe shows short response time, high sensitivity and selectivity. TPAMA-HCCP-PEG is amphiphilic and shows high water dispersibility and low cytotoxicity. TPAMA-HCCP-PEG can be used for detection of ClO − in living systems.